EFEKTIFITAS PENGGUNAAN MEDIA KARTU WARNA TERHADAP KETRAMPILAN MENULIS PANTUN SISWA KELAS IV SD INPRES ANDI TONRO KOTA MAKASSAR - Amelia Putri; Andi Paida; Rahmatia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Amelia, Putri. 2025. The Effectiveness of Using Color Card Media on the Skills of Writing Pantun of Fourth Grade Students at SD Inpres Andi Tonro, Makassar City. Thesis, Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Makassar. Supervisor I: Andi Paida and Supervisor II: Rahmatiah. The main problem in this study is whether there is an effect of using color card media on the skills of writing pantun among fourth grade students at SD Inpres Andi Tonro, Makassar City. This research is a quantitative experimental study (pre- experimental). The experimental study employed a one-group pretest–posttest design. In this design, the experimental class was given a learning model using color card media. The sample of this study was the fourth grade B students of SD Inpres Andi Tonro, Makassar City. The results of this study show that: (1) The percentage of achievement standards obtained from the pretest scores (before treatment) using color card media was very low, (2) The percentage of achievement standards obtained from the posttest scores (after treatment) using color card media was categorized as high, (3) The use of color card media was effective and able to improve learning outcomes in the skill of writing pantun for fourth grade students at SD Inpres Andi Tonro, Makassar City. Based on these results, it can be concluded that the use of color card media is effective in improving the skill of writing pantun of fourth grade students at SD Inpres Andi Tonro, Makassar City.